Real-world burden of systemic lupus erythematosus in the USA: a comparative cohort study from the Medical Expenditure Panel Survey (MEPS) 2016–2018. Issue 1 (24th May 2022) - Grabich, Shannon; Farrelly, Eileen; Ortmann, Robert; Pollack, Michael; Wu, Sandra Sze-jung
Abstract : Objective: SLE is a chronic, multiorgan, autoimmune disease; however, current prevalence estimates are dated and often from non-generalisable patient populations, and quality of life and patient-reported outcomes in the real-world SLE population are not well-published. The present study used the Medical Expenditure Panel Survey (MEPS), a generalisable US data source encompassing a representative sample of regions/payers, to estimate SLE prevalence and characterise disease burden compared with non-SLE respondents. Methods: Retrospective population-based survey data weighted to the full US population from MEPS for the calendar years 2016–2018, pooled over the full study period, was used. The primary inclusion criteria included adults with self-reported SLE and either a record of SLE-related medication and/or rheumatologist visit in the calendar year. A matched-control cohort was created and the general non-SLE MEPS population was matched to MEPS SLE respondents by gender, age, region and MEPS reporting year using a 1:5 ratio. Results: From 2016 to 2018, 96 996 adults reported annual data in MEPS, of whom 154 respondents met the primary SLE definition, equivalent to 490 385 weighted number of adults with SLE. The prevalence of SLE was 195 (95% CI 149 to 242) per 100000, with greater prevalence observed in the US South, African-American/black and publicly insured people and females. SLE respondents reported limitations in physical function at 3 times greater rate (45% vs 15%; p<0.0001), higher rates of pain-limiting work (67% vs 39%; p<0.001) and feeling depressed 'nearly every day' (7% vs 2%; p<0.001) compared with non-SLE respondents. All-cause healthcare and prescription expenses were significantly higher in SLE respondents (US$17 270 vs US$8350 (p < 0.0001) and US$4512 vs US$1952 (p < 0.001), respectively, in 2018 US dollars). Conclusion: Wide variation of SLE prevalence exists among patients of different regional, demographic and payer groups; SLE is associated with adverse quality of life, productivity and economic outcomes compared with non-SLE respondents.